CHANGES IN HYDROGEOLOGICAL CONDITIONS DURING BOGGING IN THE SOUTHEAST OF THE WEST SIBERIAN PLAIN - Oleg G. Savichev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Link for citation: Savichev O.G. Changes in hydrogeological conditions during bogging in the southeast of the West Siberian plain. Bulletin of the Tomsk Polytechnic University. Geo Аssets Engineering, 2023, vol. 334, no. 10, рр. 187-198. In Rus.